Implementasi Strategi Pemerintah Dalam Mewujudkan Desa Anti Politik Uang Di Desa Sardonoharjo Kecamatan Ngaglik Daerah Istimewa Yogyakarta - Poliman Padang; Julia Ivana (Universitas 17 Agustus 1945 Semarang, 2022)
Implementation of the Government's Strategy in Creating an Anti-Money Politics Village is a strategy carried out by the government, namely in the form of a Program to anticipate the practice of money politics or Money Politics in Elections. The aim of this research was to provide readers with an understanding of what strategies can be used to eradicate political money practices in a democracy. The research method that researchers use is descriptive research. The focus of the research is on what strategies or tactics are used by the government to eradicate the practice of money politics and what obstacles are experienced in implementing these strategies. The solution to this problem is encouragement for the government, community leaders and parents to launch this strategy.